Characterization of the immune response induced by pertussis OMVs-based vaccine. Issue 28 (14th June 2016) - Bottero, D.; Gaillard, M.E.; Zurita, E.; Moreno, G.; Martinez, D. Sabater; Bartel, E.; Bravo, S.; Carriquiriborde, F.; Errea, A.; Castuma, C.; Rumbo, M.; Hozbor, D.
Highlights: TdapOMVs Bp vaccine induces a mixed Th1/Th2 and Th17 immune response. TdapOMVs Bp vaccination induces a robust antibody response with a high IgG2a/IgG1 rate. TdapOMVs Bp -raised antibodies partially protect against B. pertussis infection. B. pertussis was efficiently opsonized by both TdapOMVs Bp and wP-induced serum antibodies. GroEL, OMPc, PTx, PRN and Fim were identified as the main OMVs immunogens. Abstract: For the development of a third generation of pertussis vaccine that could improve the control of the disease, it was proposed that the immune responses induced by the classic whole cell vaccine (wP) or after infection should be used as a reference point. We have recently identified a vaccine candidate based on outer membrane vesicles (OMVs) derived from the disease etiologic agent that have been shown to be safe and protective in mice model of infection. Here we characterized OMVs-mediated immunity and the safety of our new candidate. We also deepen the knowledge of the induced humoral response contribution in pertussis protection. Regarding the safety of the OMVs based vaccine (TdapOMVs Bp, ) the in vitro whole blood human assay here performed, showed that the low toxicity of OMVs-based vaccine previously detected in mice could be extended to human samples. Stimulation of splenocytes from immunized mice evidenced the presence of IFN-γ and IL-17-producing cells, indicated that OMVs induces both Th1 and Th17 response. Interestingly TdapOMVs Bp -raised antibodies such as those induced by wP and commercial acellular vaccines (aP) which contribute to induce protection against Bordetella pertussis infection. As occurs with wP-induced antibodies, the TdapOMVsBp-induced serum antibodies efficiently opsonized B. pertussis . All the data here obtained shows that OMVs based vaccine is able to induce Th1/Th17 and Th2 mixed profile with robust humoral response involved in protection, positioning this candidate among the different possibilities to constitute the third generation of anti-pertussis vaccines.